1990
DOI: 10.2337/diab.39.3.354
|View full text |Cite
|
Sign up to set email alerts
|

Microvascular Reactivity to Norepinephrine at Different Arteriolar Levels and Durations of Streptozocin-Induced Diabetes

Abstract: Microvascular disease is a hallmark of diabetes. Although the etiology of diabetic microangiopathy remains to be elucidated, numerous studies in experimental animals and human diabetic patients have suggested that a change in vascular reactivity to vasoactive agents is a component of the pathophysiology. Most previous studies have utilized indirect methods to study the microcirculation or have conducted studies of responses in large vessels. This study was designed to directly study in an intact microvascular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
13
0

Year Published

1992
1992
1996
1996

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(15 citation statements)
references
References 23 publications
2
13
0
Order By: Relevance
“…The hyporesponsiveness to phenylephrine demonstrated postsynaptic defects confirming other observations of decreased noradrenaline responsiveness (Foy & Lucas, 1976;Jackson & Carrier, 1983;Ramos, 1988; Van der Zee et al, 1990) in diabetes mellitus. Increased noradrenaline responsiveness has also been described (White & Carrier, 1990;Morff, 1990). As we are the first to measure noradrenaline responsiveness in the vasa nervorum of diabetic rats, comparison of our results with previous research in other vascular systems is difficult.…”
Section: Discussionmentioning
confidence: 74%
“…The hyporesponsiveness to phenylephrine demonstrated postsynaptic defects confirming other observations of decreased noradrenaline responsiveness (Foy & Lucas, 1976;Jackson & Carrier, 1983;Ramos, 1988; Van der Zee et al, 1990) in diabetes mellitus. Increased noradrenaline responsiveness has also been described (White & Carrier, 1990;Morff, 1990). As we are the first to measure noradrenaline responsiveness in the vasa nervorum of diabetic rats, comparison of our results with previous research in other vascular systems is difficult.…”
Section: Discussionmentioning
confidence: 74%
“…These include alterations to both the purinergic (Belai et al, 1991) and peptidergic (Belai et al, 1987;D'Amato & Curro, 1990) components of rat gastrointestinal tissue, and impaired NANC neurotransmission in human corporal smooth muscle from impotent diabetic men (Saenz de Tejada et al, 1989). Furthermore, previous studies have demonstrated that the development of diabetes-induced changes may depend on the duration of the diabetic state (MacLeod & McNeill, 1985;Belai et al, 1988;Morff, 1990;Nowak et al, 1990). For example, in the myenteric plexus of STZ-diabetic rats, biochemical results showed a trend at 8 weeks for an increase in noradrenaline content, followed by a decrease in both tissue content and nerve fibre density at 16 and 24 weeks after diabetes induction (Belai et al, 1988).…”
Section: Discussionmentioning
confidence: 99%
“…Since the arterioles are the major site of vascular resistance, small changes in arteriolar sensitivity could have a significant effect on blood pressure, and the regulation of tissue blood flow (Morff, 1990).…”
Section: Discussionmentioning
confidence: 99%